SAFETY CONSIDERATIONS WITH BLOOD FLOW RESTRICTED RESISTANCE TRAINING - Alan Kacin; Benjamin Rosenblatt; Tina Grapar Žargi; Anita Biswas (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Blood flow restricted resistance (BFRR) training with pneumatic tourniquet has been suggested as an alternative for conventional weight training due to the proven benefits for muscle strength and hypertrophy using relatively low resistance, hence reducing the mechanical stress across a joint. As such, it has become an important part of rehabilitation programs used in either injured or operated athletes. Despite a general consensus on effectiveness of BFRR training for muscle conditioning, there are several uncertainties regarding the interplay of various extrinsic and intrinsic factors on its safety and efficiency, which are being reviewed from a clinical perspective. Among extrinsic factors tourniquet cuff pressure, size and shape have been identified as key for safety and efficiency. Among intrinsic factors, limb anthropometrics, patient history and presence of cardiac, vascular, metabolic or peripheral neurologic conditions have been recognized as most important. Though there are a few potential safety concerns connected to BFRR training, the following have been identified as the most probable and health-hazardous: (a) mechanical injury to the skin, muscle, and peripheral nerves, (b) venous thrombosis due to vascular damage and disturbed hemodynamics and (c) augmented arterial blood pressure responses due to combined high body exertion and increased peripheral vascular resistance. Based on reviewed literature and authors' personal experience with the use of BFRR training in injured athletes, some guidelines for its safe application are outlined. Also, a comprehensive risk assessment tool for screening of subjects prior to their inclusion in a BFRR training program is being introduced.